1977
DOI: 10.7164/antibiotics.30.541
|View full text |Cite
|
Sign up to set email alerts
|

Fortimicins A and B, new aminoglycoside antibiotics. II. Isolation, physico-chemical and chromatographic properties.

Abstract: Thin-layer chromatography of the mixed neomycin sulfates on carbon plates. Anal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The results of these studies are also'shown in Table 4. DISCUSSION Fortimicin A and B are novel new disaccharide aminoglycosides produced by M. olivoasterospora (2,5,10,11). The structural qualities of fortimicin A protect it from most commonly encountered aminoglycoside-inactivating enzymes (10,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies are also'shown in Table 4. DISCUSSION Fortimicin A and B are novel new disaccharide aminoglycosides produced by M. olivoasterospora (2,5,10,11). The structural qualities of fortimicin A protect it from most commonly encountered aminoglycoside-inactivating enzymes (10,12).…”
mentioning
confidence: 99%
“…Fortamine cyclitol-containing antimicrobials were obtained from Micromonospora olivoasterospora (2,10,11). The most promising compound, fortimicin A (XK-70-1), is a novel pseudodisaccharide antibiotic with chiro cyclitol stereochemistry ( Fig.…”
mentioning
confidence: 99%
“…Fortimicin B is a member of the fortimicins, which are potent broad-spectrum aminocyclitol antibiotics produced by a strain of Micromonospora olivoasterospona Okachi et aL, 1977). X-ray structure determination of the title molecule was carried out in order to confirm the structure proposed from chemical and spectroscopic evidence (Egan et al, 1977) and to determine the absolute configuration unequivocally.…”
Section: Structure Of Fortimicin Bmentioning
confidence: 99%
“…Biotransformation products were detected by means of carbon- 7 ) and silica gel-thin layer chromatography (TLC) and paper chromatography using the following solvent systems: the lower phase of chloroform-methanol-concentrated ammonium hydroxide (1: 1: 1, v/v) for silica gel-TLC, 2: 1: 1 (v/v) (17% ammonium hydroxide) for paper chromatography and 0.5 N hydrochloric acid-methanol (20: 1, v/v) for carbon TLC. Antibiotic zones on the chromatograms were detected by bioautography against Bacillus subtilis, or by Rydon-Smith reagent.…”
Section: Microorganismsmentioning
confidence: 99%